Nutritional composition of mungbean and soybean sprouts compared to their adult growth stage. (15th December 2017) - Ebert, Andreas W.; Chang, Ching-Huan; Yan, Miao-Rong; Yang, Ray-Yu
Highlights: Older mungbean varieties were nutritionally superior to improved lines at full maturity. Sprouting mungbeans enhanced vitamin C content 2.7-fold compared to mature grain. Vegetable soybean was nutritionally superior to soybean sprouts. Nutrient and antioxidant contents of soybean sprouts were superior to mungbean sprouts. Abstract: This study determined the level of phytonutrients in mungbean and soybean sprouts compared to mature mungbean grain and vegetable soybean. The comparison included landraces and improved mungbean and soybean varieties to assess the effect of breeding on the phytonutrient content of both crops. Sprouting mungbean enhanced vitamin C content 2.7-fold compared to mature mungbean grain. Relatively old mungbean accessions were superior in protein, calcium (Ca), iron (Fe), zinc (Zn), carotenoid and vitamin C content compared to improved mungbean lines at the fully mature stage. With regard to nutritional value, the vegetable soybean stage was superior to soybean sprouts in terms of content of protein (14% increase), Zn (45%), Ca (72%), and Fe (151%). Isoflavones, reported to have beneficial effects on human health, are found at high concentrations in soybean sprouts and could easily provide the recommended anticarcinogenic dose range from 1.5 to 2.0 mg/kg of body weight per day.